2021
DOI: 10.1002/mpr.1882
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of early cognitive training and rehabilitation for patients with cognitive dysfunction in stroke

Abstract: Objective: This article explores the effects of early cognitive training and rehabilitation for patients with cognitive dysfunction in stroke. Methods: Stroke patients have cognitive dysfunction, and the incidence of cognitive dysfunction in stroke patients is six to nine times that of patients without stroke. This article selects 118 patients with stroke in our hospital from August 2017 to August 2019, 42 patients with stroke disorders randomly divided into two groups. Both groups of patients received convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[ 2 ] The incidence of cognitive impairment is six-to-nine times higher in stroke survivors than that in survivors without stroke, with adverse repercussions for themselves, their families, and society at a large. [ 3 ]…”
Section: B Ackgroundmentioning
confidence: 99%
“…[ 2 ] The incidence of cognitive impairment is six-to-nine times higher in stroke survivors than that in survivors without stroke, with adverse repercussions for themselves, their families, and society at a large. [ 3 ]…”
Section: B Ackgroundmentioning
confidence: 99%
“…Users can interact with objects in the virtual world naturally, through special input and output devices, and experience the same feelings as in the real world through vision, hearing and touch (Mishkind et al, 2017; Perpiñá‐Galvañ et al, 2021). At present, VR technology is mainly applied in clinical teaching, stomatology, surgical simulation, telemedicine, rehabilitation healthcare, psychological treatment and other aspects of the medical field (Clerc et al, 2021; Knaust et al, 2020; Nunna et al, 2019; Qi et al, 2021; Vieira et al, 2018; Xuefang et al, 2021). As a relatively novel intervention measure, VR technology on adult preoperative anxiety is mainly achieved through distraction and virtual reality exposure (VRE) (Han et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cognitive training based on arti cial intelligence has been applied to the cognitive treatment of dementia patients and psychiatric patients at home and abroad. Studies have shown that the effect of cognitive training based on arti cial intelligence can achieve the same effect as that of arti cial cognitive training [11] , which can solve problems such as insu cient and uneven distribution of rehabilitation resources and repetitive and boring contents of traditional arti cial cognitive training that rely on therapist techniques, which makes it di cult to achieve the best prognosis [12] .…”
Section: Introductionmentioning
confidence: 99%